The effect of teaching using electronic visual notation in developing the skills of jurisprudence of inheritance among secondary school students - Altalhi, Huda Muhsiny; Al Tameem, Abdullah Mohamad Ayed (Journal of Educational and Psychological Sciences, 2023)
The study aimed to verify the effect of teaching using electronic visual notation in developing the skills of jurisprudence of inheritance among secondary school students. The study sample consisted of (42) female students, divided into two groups, an experimental group consisting of (21) students, and a control group consisting of (21) female students. Of the female students of the first year of secondary school in the first secondary school in Jeddah, the study relied on the quasi- experimental method, with the two- group system. The first group: represented the experimental group to which the visual notation method was applied. The second group: It represents the control group, which was taught in the traditional way. The researcher used the cognitive achievement test as a tool for collecting information, and the most important results of the study were: This indicates that there are statistically significant differences between the mean scores of the control and experimental group members in the cognitive test in the post application in favor of the experimental group. The most important recommendations of the study were: making use of the videos that were prepared from teaching the skills of jurisprudence (the jurisprudence of inheritance), the necessity of employing visual logging in the curriculum, training female teachers on the use of visual logging in teaching and holding workshops for them on how to produce videos and various visual logging tools. One of the studies aimed at recognizing the effectiveness of electronic visual notation in developing other educational skills.